The Existence of Kaum After the Instruction of Director General of Islamic Guidance Number DJ.II/I Year 2015 from the Perspective of Structural Functionalism - Ulinnuha, Muhammad (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
Marriage Registration Officer (P3N) or in the community of Bener District, Puworejo Regency, familiarly called Kaum, is often used by couples who will carry out marriage. The task of the people is to assist in the administration of marriage registration at the local KUA, but since the issuance of the Instruction of Bimas Islam in 2015 the people through the instruction were dismissed from their status as P3N, interestingly although the status of the people formally has now been deactivated legally so that the existence and function of the people as PPN assistants have been removed, but in fact there are still many who use the services of the people until now, especially in the Bener District area. The purpose of this study is to examine and analyze the urgency and existence of the kaum in the marriage registration perspective of structural functionalism theory. This research is field-based (Field Research) with an empirical sociological approach method, while the data source comes from primary data, namely observation and interviews, while secondary data comes from books, articles and various references relevant to the above topic. The results of this study found that couples who register marriages at the KUA of Bener Subdistrict give trust to the people to take care of all the administration needed by the KUA, besides that the people also often become witnesses from the bride's side, host, and even remarks. In the social analysis of AGIL theory, namely adaptation, goal attainment, integration and latency. The function of adaptation is in the form of the adaptation commitment of the kaum in maintaining the mandate to the community and the government, the function of achieving goals is in the form of helping the community because the kaum play a lot of roles in the marriage process such as recording marriages, being witnesses, being mc and or remarks. The village government and KUA are also helped by the existence of kaum who try to get every married couple to register their marriage with the state. The function of integration is the formation of unwritten rules regarding the cost of kaum services, and the kaum can adjust to the poor community. The latency function is in the form of kaum strengthening synergy and good communication patterns to the Ministry of Religious Affairs/KUA, village government, and the community.